A study on the factors affecting work engagement among employees in fast food industry in Malaysia - Chan, Ying Xuan; Choy, Li Hua; Foo, Wen Kei; Lai, Hor Lay (2024)
In the competitive business environment, it is particularly critical to understand the importance of work engagement among employees because work engagement among employees has a direct impact on organizational performance and development. Employees who are engaged in their work include not only completing tasks, but also enthusiasm, a positive attitude, and dedication to the work. Therefore, it has become an organization's responsibility to establish a culture and environment that stimulates employees' potential and enhances their work engagement. In the fast food industry in Malaysia, employee turnover is high because many employees view their jobs as temporary rather than permanent. Although there has been much research on employee work engagement, relatively little research has been conducted in the fast food industry, mostly focusing on areas such as the hospitality, healthcare, and telecommunication industries. Therefore, this study chose to use quantitative research to explore work engagement among employees in the fast food industry. In order to collect data, 377 questionnaires were distributed to McDonald's employees in Perak, Malaysia through Google Forms in order to obtain their feedback. After collecting the questionnaire, the data were analysed using Statistical Package for Social Sciences (SPSS). Cronbach's alpha reliability test, Pearson's correlation coefficient, and multiple regression analysis were used in the study to assess the relationship between the dependent variable (work engagement) and the independent variables (leadership, training and development, communication, and reward). The results showed that there was a significant positive correlation between the independent variables and the dependent variables.